2018
DOI: 10.2298/fil1810549b
|View full text |Cite
|
Sign up to set email alerts
|

Pointwise planar horizontal sections along Riemannian submersions

Abstract: We study Riemannian submersions with pointwise k-planar horizontal sections. We provide examples, obtain characterizations and give a geometric interpretation of such property.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Such submanifolds were studied widely by many authors and many nice geometric properties of such submanifolds have been found, see [11]. On the other hand, the notion of planar horizontal sections for Riemannian submersions has been introduced in [7].…”
Section: Introductionmentioning
confidence: 99%
“…Such submanifolds were studied widely by many authors and many nice geometric properties of such submanifolds have been found, see [11]. On the other hand, the notion of planar horizontal sections for Riemannian submersions has been introduced in [7].…”
Section: Introductionmentioning
confidence: 99%